Factors influencing males’ loyalty toward functional foods during the COVID-19 pandemic - Sik Sumaedi; Sumardjo Sumardjo; Amiruddin Saleh; Agus Fanar Syukri (Intelektual Pustaka Media Utama, 2022)
Coronavirus disease 2019 (COVID-19) is a serious issue nowadays. Several studies showed that male was more vulnerable to COVID-19 than female. Functional food consumption can be used to overcome COVID-19 since it boosts someone’s immune system and reduces the risk of contracting non-communicable diseases simultaneously. It is important to improve males’ functional food loyalty during the COVID-19 pandemic. However, there is lack of research on males’ functional food loyalty during the COVID-19 pandemic. Given this, this research aims to test the effect of perceived threat of COVID-19, perceived benefit of functional food related to COVID-19, e-health literacy, digital health communication media usage, attitude toward functional food, functional food accessibility, and social influences-injunctive norm and descriptive norm–on males’ functional food loyalty during the COVID-19 pandemic. This study collected data through a survey. It involved 204 male respondents in Banten, Indonesia. This research found that males’ functional food loyalty during the COVID-19 pandemic was significantly and positively affected by attitude toward functional food, injunctive norm, food accessibility and digital health communication usage. However, males’ functional food loyalty was not significantly affected by the perceived threat of COVID-19, perceived benefit of functional food related to COVID-19, descriptive norm and e-health literacy.